A New Voltammetric Approach for Electrochemical Determination of Lamotrigine in Pharmaceutical Samples. Issue 6 (22nd March 2021) - Ciucu, Anton A.; Buleandră, Mihaela; Ciurea, Tatiana; Stoica, Vlad N.; Ştefanescu, Cristian D.; Ciobanu, Adela
Abstract: A new linear sweep voltammetric method for quantitative lamotrigine (LMT) determination based on an electrochemically pre‐treated pencil graphite electrode (PGE*) is presented. Response characteristics of the PGE* toward the mentioned compound were investigated by cyclic voltammetry and linear sweep voltammetry. The quantitative determination of LMT revealed a wide linear range of 2.5 ⋅ 10 −5 –1.0 ⋅ 10 −3  M with a detection limit of 1.94 ⋅ 10 −5  M. The method was used successfully for LMT determination in a pharmaceutical formulation. Abstract :